Effects of in situ Remediation With Nanoscale Zero Valence Iron on the Physicochemical Conditions and Bacterial Communities of Groundwater Contaminated With Arsenic - Castaño, Ana; Prosenkov, Alexander; Baragaño, Diego; Otaegui, Nerea; Sastre, Herminio; Rodríguez-Valdés, Eduardo; Gallego, José Luis R.; Peláez, Ana Isabel (Frontiers in Microbiology, 2021)
Nanoscale Zero-Valent Iron (nZVI) is a cost-effective nanomaterial that is widely used to remove a broad range of metal(loid)s and organic contaminants from soil and groundwater. In some cases, this material alters the taxonomic and functional composition of the bacterial communities present in these matrices; however, there is no conclusive data that can be generalized to all scenarios. Here we studied the effect of nZVI application in situ on groundwater from the site of an abandoned fertilizer factory in Asturias, Spain, mainly polluted with arsenic (As). The geochemical characteristics of the water correspond to a microaerophilic and oligotrophic environment. Physico-chemical and microbiological (cultured and total bacterial diversity) parameters were monitored before and after nZVI application over six months. nZVI treatment led to a marked increase in Fe(II) concentration and a notable fall in the oxidation-reduction potential during the first month of treatment. A substantial decrease in the concentration of As during the first days of treatment was observed, although strong fluctuations were subsequently detected in most of the wells throughout the six-month experiment. The possible toxic effects of nZVI on groundwater bacteria could not be clearly evidenced by direct observations of those stained with viability dyes. The number of cultured bacteria increased during the first two weeks of the treatment, although this was followed by a continuous decrease for the following two weeks, reaching levels moderately below the initial number at the end of sampling, and by changes in their taxonomic composition. Most bacteria were tolerant to high As(V) concentration and showed the presence of diverse As resistance genes. A more complete study of the structure and diversity of the bacterial community of the groundwater using automated ribosomal intergenic spacer analysis (ARISA) and sequencing of the 16S rRNA amplicon by Illumina MiSeq confirmed the presence of significant alterations of its composition, with a reduction in richness and diversity (the latter evidenced by Illumina data) after treatment with nZVI. The anaerobic conditions stimulated by treatment favored the development of sulfate-reducing bacteria, thereby opening up the possibility to achieve more efficient removal of As.